Alternatives to Autologous Bone Graft in Alveolar Cleft Reconstruction: The State of Alveolar Tissue Engineering. Issue 3 (May 2018) - Liang, Fan; Leland, Hyuma; Jedrzejewski, Breanna; Auslander, Allyn; Maniskas, Seija; Swanson, Jordan; Urata, Mark; Hammoudeh, Jeffrey; Magee, William
Abstract : Abstract: Alveolar cleft reconstruction has historically relied on autologous iliac crest bone grafting (ICBG), but donor site morbidity, pain, and prolonged hospitalization have prompted the search for bone graft substitutes. The authors evaluated bone graft substitutes with the highest levels of evidence, and highlight the products that show promise in alveolar cleft repair and in maxillary augmentation. This comprehensive review guides the craniofacial surgeon toward safe and informed utilization of biomaterials in the alveolar cleft. A literature search was performed to identify in vitro human studies that fulfilled the following criteria: Level I or Level II of evidence, ≥30 subjects, and a direct comparison between a autologous bone graft and a bone graft substitute. A second literature search was performed that captured all studies, regardless of level of evidence, which evaluated bone graft substitutes for alveolar cleft repair or alveolar augmentation for dental implants. Adverse events for each of these products were tabulated as well. Sixteen studies featuring 6 bone graft substitutes: hydroxyapatite, demineralized bone matrix (DBM), β-tricalcium phosphate (TCP), calcium phosphate, recombinant human bone morphogenic protein-2 (rhBMP-2), and rhBMP7 fit the inclusion criteria for the first search. Through our second search, the authors found that DBM, TCP, rhBMP-2, and rhBMP7 have been studied most extensively in the alveolar cleft literature, though frequently in studies using less rigorous methodology (Level III evidence or below). rhBMP-2 was the best studied and showed comparable efficacy to ICBG in terms of volume of bone regeneration, bone density, and capacity to accommodate tooth eruption within the graft site. Pricing for products ranged from 290 to 3110 per 5 mL. The balance between innovation and safety is a complex process requiring constant vigilance and evaluation. Here, the authors profile several bone graft substitutes that demonstrate the most promise in alveolar cleft reconstruction.